Fragile X syndrome with FMR1 and FMR2 deletion. Issue 7 (1st July 1999) - Moore, S J; Strain, L; Cole, G F; Miedzybrodzka, Z; Kelly, K F; Dean, J C S
Abstract : We report a 13 year old boy with fragile X syndrome resulting from a de novo deletion of the FMR1 and FMR2 genes extending from (and including) DXS7536 proximally to FMR2 distally. The patient has severe developmental delay, epilepsy, and behavioural difficulties, including autistic features. He has epicanthic folds, in addition to facial features typical of fragile X syndrome, and marked joint hypermobility. We compare our patient to the three other cases reported in which both FMR1 and FMR2 are deleted. This case has the smallest deletion reported to date. All four patients have epilepsy and a more severe degree of mental retardation than is usual in fragile X syndrome resulting from FMR1 triplet repeat expansion. Three of the patients have joint laxity and two have epicanthic folds. We suggest that these features, in particular severe developmental delay and epilepsy, may form part of the characteristic phenotype resulting from deletion of both FMR1 and FMR2 genes. The diagnosis in this case was delayed because routine cytogenetics showed no abnormality and standard molecular tests for FMR1 triplet repeat expansion (PCR and Southern blotting) failed. Further DNA studies should be undertaken to investigate for a deletion where clinical suspicion of fragile X syndrome is strong and routine laboratory tests fail.